Transfer and Success in the Acquisition of Verbal Properties in French and English - Sheppard, Ken (Revue québécoise de linguistique, 1991)
AbstractThis study compares the acquisitional states of two groups of foreign language learners (a Francophone group learning English and an Anglophone group learning French) with a view to establishing the influence of Universal Grammar in the process. Specifically, the two groups (48 each) were asked to render acceptability judgments about 50 sentences in each language; the sentences exemplified syntactic properties [the permissability or impermissibility of fully tensed clausal complements, Exceptional Case Marking and Control structures (PRO)] associated with three verbs in the two languages (believe/croire, promise/promettre and want/vouloir).